Penggunaan Tabel Bilangan untuk Meningkatkan Hasil Belajar Siswa Tentang Akar Pangkat Tiga di Sekolah Dasar - Hermalindawati Hermalindawati (Pedagogi: Jurnal Ilmu Pendidikan, 2018)
This study aims to improve the primary schools learning on subjects mathematics with material cube root. Conventional methods do teachers in learning activities mathematics make the student’s hard to understand and complete the task. this with proven results learns obtained students well below the standard. With the help of the table, numbers cube is expected to students can be easier to understand and resolve problems related to the cube root. research methods used is a class action research aimed at improving learning done teacher so that the student learning outcomes increase. The results indicate that the student learning outcome increase. So it can be concluded that the use of the table numbers cube can increase the understanding and student learning outcomes in material cube root.